The Effect of Industrial Practice Experience on Student's Work Readiness of Machinery Engineering Vocational School - Larosa, Esta; Gani, Imam Prawiranegara; Mbakwa, Patterson Nji (Universitas Muhammadiyah Mataram, 2022)
This study aims to reveal the effect of industrial practice experience on the job readiness of vocational engineering mechinery students in Yogyakarta. This type of research is ex-post facto with a correlational approach. The subjects in this study were all students of machining engineering expertise program at Vocational High School Yogyakarta, with a total of 297 students. Determination of sample size using the Isaac & Michael table, obtained a sample of 247 students. Sampling with purposive sampling technique and data collection using a questionnaire. The data analysis technique used is descriptive statistics to describe the data of each variable and the regression analysis used for hypothesis testing. Based on the analysis and hypothesis testing, it can be concluded that the hypothesis has a positive and significant effect between industrial practice experience on the work readiness of students of Mechanical Engineering Vocational School in Yogyakarta. It can be seen from the regression results and the results of the significance of industrial practice experience on student work readiness, the correlation coefficient (r) is 0.677 and the coefficient of determination (r2) is 0.459. The results of this study indicate that the experience of industrial practice has a positive and significant effect on the work readiness of Mechanical Engineering students at Mechanical Engineering Vocational School in Yogyakarta.